Incentivising bioenergy with carbon capture and storage (BECCS) responsibly: Comparing stakeholder policy preferences in the United Kingdom and Sweden. Issue 116 (February 2021) - Bellamy, Rob; Fridahl, Mathias; Lezaun, Javier; Palmer, James; Rodriguez, Emily; Lefvert, Adrian; Hansson, Anders; Grönkvist, Stefan; Haikola, Simon
Highlights: Responsible incentivisation requires attention to situated stakeholder perspectives. We develop four policy scenarios and subject them to deliberation in the UK and Sweden. New incentives and enabling reforms to existing policy instruments are needed. Mitigation deterrence must be considered in real world (not abstracted) contexts. Multi-instrument approaches are needed to overcome single instrument deficiencies. Abstract: Bioenergy with carbon capture and storage (BECCS) plays a central role in scenario pathways that limit global warming in line with the objectives of the Paris Agreement. Yet deliberate policy efforts to incentivise BECCS—whether through amending existing climate policies or introducing entirely new ones—remain rare. In this paper, we contend that BECCS must be incentivised responsibly, through policy-making processes which account for diverse and geographically varying societal values and interests. More specifically, we make the case for responsible incentivisation by undertaking a comparative analysis of stakeholder attitudes to four idealised policy scenarios for BECCS, including representatives of government, business, nongovernmental and academic communities, in the UK and Sweden. The scenarios were: business as usual; international policy reform; national BECCS policy; and national policy for negative emissions technologies. Based on our findings, we recommend that policymakers 1) recognise the need to develop new incentives and make enabling reforms to existing policy instruments; 2) consider the risk of mitigation deterrence in their real world (and not abstracted) contexts; 3) employ multi-instrument approaches to incentivisation that do not overly rely on carbon pricing or 4) force a choice between technology specific or technology neutral policies; and 5) attend to the diversity of stakeholder and wider public perspectives that will ultimately determine the success—or failure—of their policy designs.